Adaptation of the abuse assessment screening tool for midwives in northern Nigeria - Musa-Maliki, Ayishetu Uduoye (Department of Health and Rehabilitation Sciences, 2019)
The term „intimate partner violence‟ (IPV) is employed in this study to denote the physical, sexual, economic, and psychological or other harm directed against a pregnant woman by her partner or spouse. It affects both pregnant women and their unborn children, as both may suffer serious health consequences. The purpose of this study is to investigate midwives‟ current screening practice for IPV among pregnant women in a northern Nigerian hospital and to adapt the Abuse Assessment Screen (AAS) tool to aid midwives‟ screening practice. Qualitative data were collected from midwives in the antenatal clinic of Ahmadu Bello University Teaching Hospital, Zaria, Nigeria, in four phases using a panel longitudinal design as a guide. In the first phase non-participant observation and individual face-to-face semistructured interviews were conducted with ten participants using an interview guide. In phase two non-participant observation of the same participants took place as pregnant women were screened with the original AAS tool for two months, then a focus group discussion was conducted in phase three. Thematic data analysis was carried out in all phases using Yin‟s five stages of analytical cycle and also guided by the conceptual framework of Wile‟s human technology model. In phase four the original AAS tool was modified based on the findings of phases two and three. Five themes emerged in phase one and four in phase three after triangulation of data from phase two. It was found that routine screening for IPV is not practiced by midwives in the research setting as a result of various factors, some internal and others external to them. The midwives also faced several challenges that discourage screening of pregnant women for IPV. Their suggested solutions to these challenges were also incorporated into a modified version of the original AAS tool after analysing the data. Thereafter the modified tool was given to the same participants to use and to confirm its suitability for IPV screening in phase four, and a theme emerged. With adequate education and training the internal factors hindering midwives‟ screening practice can be eliminated, while the external factors will need the intervention of hospital authorities to eliminate or mitigate their effects on screening.